2013
DOI: 10.1186/1743-8977-10-22
|View full text |Cite
|
Sign up to set email alerts
|

Placental DNA hypomethylation in association with particulate air pollution in early life

Abstract: BackgroundThere is evidence that altered DNA methylation is an important epigenetic mechanism in prenatal programming and that developmental periods are sensitive to environmental stressors. We hypothesized that exposure to fine particles (PM2.5) during pregnancy could influence DNA methylation patterns of the placenta.MethodsIn the ENVIRONAGE birth cohort, levels of 5’-methyl-deoxycytidine (5-mdC) and deoxycytidine (dC) were quantified in placental DNA from 240 newborns. Multiple regression models were used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
132
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 178 publications
(138 citation statements)
references
References 68 publications
4
132
0
2
Order By: Relevance
“…29 Epigenetic modifications represent a potential link between adverse insults and altered fetal development. Previously, we have shown that PM 2.5 exposure during pregnancy affects global DNA methylation levels in placental tissue, 30 while in this study, we investigated the impact of PM 2.5 exposure upon epigenetics of placental mitochondria. Using the bisulfite-pyrosequencing approach, we were able to detect subtle differences in methylation levels of specific regions in the mitochondrial genome (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…29 Epigenetic modifications represent a potential link between adverse insults and altered fetal development. Previously, we have shown that PM 2.5 exposure during pregnancy affects global DNA methylation levels in placental tissue, 30 while in this study, we investigated the impact of PM 2.5 exposure upon epigenetics of placental mitochondria. Using the bisulfite-pyrosequencing approach, we were able to detect subtle differences in methylation levels of specific regions in the mitochondrial genome (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…As described previously, 30 we took villous tissue (1 to 2 cm 3 ) at a fixed location from the fetal side of the placenta, approximately 1-1.5 cm below the chorio-amniotic membrane, and preserved the biopsies at -80 C. Chorio-amniotic membrane contamination was avoided by careful visual examination and dissection.…”
Section: Placental Samplingmentioning
confidence: 99%
“…While all of the above studies were conducted in adults, previous research suggests that early developmental periods are particularly vulnerable to epigenetic dysregulation in response to environmental exposures [18,34]. Both human and animal models of prenatal exposure provide evidence that increased DNA adducts and global hypomethylation induce genomic and chromosomal instability [18,34].…”
Section: Pah B[a]p and Dna Methylationmentioning
confidence: 99%
“…Both animal models and human studies implicate the intrauterine period as a sensitive time for the establishment of epigenetic variability (Heijmans et al 2008;Cook et al 2007;Tang et al 2012;Radford et al 2014;Janssen et al 2013), which in turn influences risk for a range of disorders that develop later in life. In the Boston Birth Cohort, we observed a wide range of interindividual variations in genome-wide methylation at birth (Wang et al 2012).…”
Section: Gene and Environment Interaction And Epigeneticsmentioning
confidence: 99%